Perancangan UI/UX Website Pengontrol Kelembapan Tanah Berbasis IoT dan Sensor - Kynta, Diva Putri; Laksono, Ivan Luthfi; Wijaya, Vannes; Fadli, Muhammad; Hermanto, Dedy (MDP Student Conference, 2024)
Soil moisture is an important factor in agriculture, affecting plant health and crop productivity. Indonesia has experienced droughts that resulted in crop failure of 1,177 (31.95%) hectares out of a total of 3,685 hectares of agricultural land. With the arrival of the industrial era 5.0, there is an opportunity to improve soil moisture management. This research aims to design the UI/UX of an IoT and sensor-based soil moisture control website application. This system is designed to make it easier for farmers to monitor and manage soil moisture, so as to improve irrigation efficiency and crop quality. The method used in the design process of this application is the Design Thinking method. The final result obtained from this research is a User Interface and User Experience that can be a solution to existing problems. 61% of 12 respondents stated that the UI design of KeTan was very good, and 42% of 12 respondents gave very good scores for the UX of KeTan.